Unia realna angielsko-szkocka w ujęciu historiografii szkockiej XX w. Od kontynuacji do rewizji - Nowakowska-Dryk, Anna (Acta Universitatis Lodziensis. Folia Historica, 2001)
The article is condensed outlok of a Polish historian on the issue of the real Union of Great Britain from the Socottish scientific perspective. It shows several opinions on the subject, formulated by the contemporary Scottish historians. The works cited in the article prosent various historiographic attitudes, thus giving readers, a wide spectrum both of the knowledge range and the views concerning the 1707 Union, which are characteristic for the prosent-day Socottish historiography. A number of interesting questions arise in connection with the subject, to which historians give different answers. The article reveals lots of social and economic relations as well as the deliberate actions of the Union creators, which made the Union come into being. This example explains the specifics of the Scottish historiography as a distinct kind of British historiography. The Scottish point of view on the subject is a thorough one, although the emphasis is on the issues which are different from those being in the centre of attention in the history of the southern part of the Island. The Scottish interpretations may even surprise readers not only with a new attitude towards the facts but also with logic and accurcy of the conclusions. The Scottish historians have varied opinions about the main actors of the 1707 drama. This specific historiography is less known to Polish readers and remains frequently unnoticed by the history researchers outside the British cultural circles. Nevertheless, if one takes a closer look at that kind of British historiography, it appears to be methodologically mature and rich in new solutions. The article does not explore the subject comprehensively, it serves as an introduction to the mood and the problems which are predominant in the Scottish historiographic study concerning the 1707 Union.